THE IMPACT OF EMOTIONAL CONVERSATIONAL AI ON CONSUMER ENGAGEMENT AND LOYALTY - DR. SAMPADA (HASTAK) WASADE (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Conversational Artificial Intelligence (AI) has emerged as a powerful tool for shaping consumer behavior and elevating emotional engagement across digital platforms. This study explores the intersection of conversational AI and emotional marketing, focusing on how these technologies influence consumer engagement, brand perception, and loyalty. Using a mixed-method approach integrating content analysis and consumer response surveys, the research examines emotional triggers embedded in chatbots and voice assistants and evaluates their effects on engagement metrics. The findings indicate that conversational AI equipped with emotional intelligence significantly increases emotional resonance, consumer satisfaction, and brand loyalty. The study offers implications for marketers, AI designers and consumer behaviour researchers. It also identifying ethical challenges and trust issues associated with emotionally aware AI systems.